Effect of tylosin on ruminal Fusobacterium necrophorum population and fermentation products in cattle fed a high-grain diet - Wallace, N.; Sun, Y.; Kemp, Kenneth E.; Parrott, J.C.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Tylosin feeding prevented the increase in Fusobacterium necrophorum population normally associated with the feeding of a high-grain diet. Also, tylosin appeared to moderate the ruminal fermentation during initial adaptation to a high-grain diet.
Keywords: Beef; Tylosin; Fusobacterium necrophorum; High-grain diet